PS-B08-2: EXOSOME-MEDIATED INTERCELLULAR CROSSTALK BETWEEN MESANGIAL CELLS AND MACROPHAGES PARTICIPATES IN THE PROGRESSION OF DIABETIC KIDNEY DISEASE. (January 2023) - Fujimoto, Daisuke; Umemoto, Shuro; Kuwabara, Takashige; Date, Ryosuke; Hata, Yusuke; Mizumoto, Teruhiko; Kakizoe, Yutaka; Izumi, Yuichiro; Mukoyama, Masashi
Abstract : Background: Extracellular vesicles (EVs) are important mediators of intercellular communication and can play a key role in the regulation of pathophysiological processes. Particularly, exosome-mediated intercellular crosstalk has been addressed in several disorders such as cancer and lifestyle-related diseases including hypertensive and diabetic vascular diseases. In diabetic kidney disease (DKD), it has been reported that macrophages infiltrate the mesangial region and may play an important role through local inflammation in glomeruli. Design and method: In this study, we focused on exosome as a factor that acts in a paracrine manner in glomeruli and examined the effects of mesangial cell-derived exosomes cultured under high-glucose conditions on macrophages. In order to identify new therapeutic agents, we screened a validated compound library that can efficiently inhibit this mechanism and also studied their effects on DKD. Results: Exosomes released from mesangial cells induced inflammation in macrophages, as indicated by the NFκB transcriptional activity and TNFα and IL-1β mRNA expression. In addition, the effect was significantly enhanced in exosomes from mesangial cells cultured under high-glucose conditions compared to low-glucose conditions. We also observed that fluorescent-labeled (DiO) exosomes were endocytosed by macrophages in vitro and in vivo. Next, we conducted drug screening using a validated compound library to find compounds that could specifically and effectively inhibit the inflammation in macrophages induced by exosomes. The screening was divided into four steps, and we succeeded in narrowing down the list to 30 candidate compounds from a total of 1, 364 compounds. Finally, an HSP90 inhibitor, alvespimycin, was identified as a compound with a strong inhibitory effect on both exosome uptake and the NFκB transcriptional activity. Treatment of a diabetic rat model with alvespimycin significantly reduced proteinuria, and showed a trend toward suppression of mesangial expansion. Conclusions: We found that mesangial cell-derived exosomes are important for inducing the local inflammation by intercellular crosstalk between mesangial cells and macrophages in DKD. Furthermore, alvespimycin, one of the HSP90 inhibitors obtained by drug screening, can effectively ameliorate the disease progression, suggesting that this mechanism could become a novel therapeutic target for DKD.